Reconfigurable THz Metamaterial Filter Based on Binary Response for Information Processing System - Ahamed, Eistiak; Tamim, Ahmed Mahfuz; Faruque, Mohammad Rashed Iqbal; Sifat, Rasheduzzaman; Islam, Mohammad Tariqul (Frontiers in Physics, 2021)
Light-matter interactions between the metallic and dielectric layers along with the controlling of electromagnetic waves can create a way to develop micro-devices and moderate the functionalities for advanced applications. This study describes a new controlling technique of the plasmatic electron packet based on an electric split-ring resonator (eSRR). All numerical experiments were performed using an advanced CST electromagnetic package. The proposed metamaterial tunnelled structure in this study operates using terahertz (THz) frequency spectrum as an efficient digital processing filter. The array combination of the tunnelled structure consisted of three individual unit cells. Moreover, the two engineered metallic arms added to the tunnelled structure exhibited two peak resonances and one passband frequency region. A large evanescent field was produced to enhance the wave-metal interactions with the presence of metal-dielectric micro-tunnel. The intensity of the electromagnetic wave-metal interactions was encoded to binary 0 and 1 for information encoding purposes. As a result, the reconfigurable micro-unit cell metamaterial tunnelled structure was able to effectively control the electric field and allow electron packets to be digitally encoded for the information processing system.